MAGNETOSTRATIGRAPHY OF THE YAHA SECTION, TARIM BASIN (CHINA): 11 MA ACCELERATION IN EROSION AND UPLIFT OF THE TIAN SHAN MOUNTAINS - Charreau J.; Chen Y.; Gilder S.; Dominguez S.; Jolivet M.; Avouac J.-P.; Sen S.; Li Y.; Wang W. (My University, 2006)
We report a magnetostratigraphic and rock magnetic study of the Yaha section, located on the southern flank of the central Tian Shan mountains, Asia. Our results show a two-fold increase in sedimentation rate as well as marked changes in rock magnetic characteristics ca. 11 Ma. After 11 Ma, sedimentation rate remained remarkably constant until at least 5.2 Ma. These findings are consistent with sedimentary records from other sections surrounding the Tian Shan. We conclude that uplift and erosion of the Tian Shan accelerated ca. 11 Ma, long after the onset of the collision between India and Asia, and that the range rapidly evolved toward a steady-state geometry via a balance between tectonic and erosion processes. © 2006 Geological Society of America.
Keywords: EROSION; MAGNETOSTRATIGRAPHY; TARIM; TIAN SHAN; UPLIFT